2019
DOI: 10.1186/s13098-019-0407-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of 6-shogaol on hyperglycemia, islet morphology and apoptosis in some tissues of streptozotocin-induced diabetic mice

Abstract: BackgroundDiabetes is characterized by hyperglycemia due to impaired insulin secretion and aberrant glucagon secretion resulting from changes in pancreatic islet cell function and/or mass. The aim of the present study was to investigate the effects of ginger on various tissues (i.e., pancreas, kidney, and liver) and insulin resistance in streptozotocin-induced diabetic mice. The pleasant aroma of ginger comes from the constituents present in its volatile oil, while its non-volatile pungent phytochemicals consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Recent diabetic mice/rats (including type I and II models) studies have shown the beneficial effects of ginger or its derivates, including 6-shogaol, on homeostatic control of blood glucose and/or insulin [36][37][38]. Moreover, the clinical trials have also found the blood glucose-lowering potential of ginger in patients with type II diabetes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent diabetic mice/rats (including type I and II models) studies have shown the beneficial effects of ginger or its derivates, including 6-shogaol, on homeostatic control of blood glucose and/or insulin [36][37][38]. Moreover, the clinical trials have also found the blood glucose-lowering potential of ginger in patients with type II diabetes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although ginger components show several anti-diabetic actions, such as reducing the levels of blood glucose and HbA1c, and decreasing the production of ROS, IL-6, and TNF-α [36,39,40,41], their mechanisms of action are not well known. 6-Shogaol inhibited AGEs-induced RAGE expression in HGFs in the present study, and it inhibited MGO-induced RAGE expression and increased HO-1 expression in human retinal epithelial cells [50], suggesting that 6-shogaol partially functions in a regulator of RAGE expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger extracts and 6-shogaol exert anti-diabetic effects including a decrease in blood glucose and HbA1c levels, and have preventive potential for DM therapy and amelioration of diabetic complications [39,40,41]. Ginger extracts may have therapeutic effects on several inflammatory diseases: 6-shogaol reduced chronic inflammation in the knees [56] and attenuated ulcerative colitis in a murine model [57], and gingerol prevented both joint inflammation and destruction in experimental rheumatoid arthritis [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ginger is one of the most famous medicinal herbs in traditional Medicine and is widely used to treat stomachache, arthritis, nonalcoholic fatty liver disease, primary dysmenorrhea, and nausea caused by pregnancy and chemotherapy [2][3][4][5][6]. In particular, the anti-diabetic effect of ginger and the gingerols, shogaols, and paradols is already known to improve insulin sensitivity and decrease the risk of diabetes mellitus [7][8][9][10]. The steaming process can affect chemicals and cause changes in biological activity.…”
Section: Introductionmentioning
confidence: 99%